Multicentre single-arm phase II trial evaluating the safety and effiCacy of Panitumumab and iRinOtecan in NeoRAS Wild-type mEtaStatic colorectal cancer patientS (C-PROWESS trial): study protocol. Issue 9 (1st September 2022) - Osumi, Hiroki; Ishizuka, Naoki; Takashima, Atsuo; Kumekawa, Yosuke; Nakano, Daisuke; Shiozawa, Manabu; Denda, Tadamichi; Sawada, Ryoichi; Ouchi, Kota; Wakatsuki, Takeru; Narikazu, Boku; Kato, Ken; et al.
Abstract : Introduction: A new concept of 'NeoRAS wild-type (WT)', which means conversion of RAS status from RAS mutant to RAS WT after treatment, has been reported. Previous observational and proof-of-concept studies have demonstrated the efficacy of epidermal growth factor receptor inhibitors in patients with NeoRAS WT metastatic colorectal cancer (mCRC). Moreover, posthoc biomarker analyses of these studies have suggested that not only the RAS status in the circulating tumour DNA (ctDNA) but also other gene mutational status may be useful as biomarkers of epidermal growth factor receptor inhibitors for NeoRAS WT mCRC. Methods and analysis: This trial is a multicentre, single-arm, phase II trial to assess the efficacy and safety of panitumumab plus irinotecan therapy for patients with NeoRAS mCRC. The key eligibility criteria include RAS mutant mCRC initially proven in tumour tissue refractory or intolerant to fluoropyrimidine, oxaliplatin and irinotecan; RAS WT in ctDNA (defined as plasma mutant allele frequencies of all RAS ≤0.1%) within 28 days before enrolment and Eastern Cooperative Oncology Group performance status ≤2. The primary endpoint is the response rate. The target sample size is 30 patients. Biomarker analyses are planned to be performed using next-generation sequencing-based ctDNA analysis. Ethics and dissemination: This study was approved by the certified review board of National Cancer Center Hospital. The main results of the trial will be presented in international meetings and in medical journals. Trial registration number: s031210565.